MAKNA KESALEHAN BAGI MUSLIM DALAM PENDEKATAN FENOMENOLOGI - Qalby, Nur; Hasanah, Miftahul; Hidayah, Mutmainna Yusra; Mustamin, Kamaruddin (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2025)
In the Islamic perspective, piety is understood as a sincere commitment by an individual to practice religious teachings, both in personal devotion and social interaction. However, in practice, piety is often narrowly interpreted as ritualistic acts of worship. Alongside the dynamics of modern life, the concept of piety has evolved to become more comprehensive—encompassing not only spiritual connection with God but also social concern and meaningful contributions to the community. This study adopts a phenomenological approach to explore the meaning of piety as experienced in diverse social and cultural contexts. The findings reveal that piety today manifests not only through religious practices such as prayer, almsgiving, and charity, but also through the expression of Islamic values in digital spaces. Furthermore, Islamic educational institutions play a crucial role in shaping the religious character of the younger generation, enabling piety to be integrated into daily life. Thus, piety is positioned as a balance between vertical devotion to God and horizontal responsibility toward fellow human beings, particularly in multicultural societies.